ANALYSIS OF THE DEVELOPMENT OF QUALITY EDUCATION AND ITS IMPACT IN REALIZING THE SUSTAINABLE DEVELOPMENT GOALS (SDGS) - Juliana Sari Br Sitompul; Debbi Chintya Ovami; Reza Hanafi Lubis; Julia Handayani; Selpida Sinurat (Universitas Efarina, 2023)
This research aims to explain and explain various strategies implemented by Indonesia in achieving the Sustainable Development Goals (SDGs) targets, especially related to improving the quality of education. The approach used in this study is qualitative descriptive, with a literature study method that gathers various relevant sources, including theories and previous research results related to the topic. Based on the results of the research, the condition of education in Indonesia is still concerning and uneven in all regions. Several provinces in Indonesia need to adopt SDGs strategies to overcome this educational inequality. It is hoped that the implementation of the SDGs program can help reduce educational inequality, as well as improve the quality of education in Indonesia, thus bringing positive changes to the country's progress.